Оценка координат космического объекта на дискретном изображении при среднем времени экспозиции кадра - Саваневич, В. Е.; Брюховецкий, А. Б. (ХНУРЭ, 2008)
Equalization of maximal likelihood verisimilitude for estimation of position of single locomotive object from data of opticelectronic mean of supervision, taking into account presence of effect of moving of object in times of display of shot and fact of sampling of image of object is got.
Keywords: космический объект; экспозиция кадра